Macrophages in Tumor Microenvironments and the Progression of Tumors - Ning-Bo Hao; Mu-Han Lü; Ya-Han Fan; Ya-Ling Cao; Zhi-Ren Zhang; Shi-Ming Yang (Clinical and Developmental Immunology)
Macrophages are widely distributed innate immune cells that play indispensable roles in the innate and adaptive immune response to pathogens and in-tissue homeostasis. Macrophages can be activated by a variety of stimuli and polarized to functionally different phenotypes. Two distinct subsets of macrophages have been proposed, including classically activated (M1) and alternatively activated (M2) macrophages. M1 macrophages express a series of proinflammatory cytokines, chemokines, and effector molecules, such as IL-12, IL-23, TNF-α, iNOS and MHCI/II. In contrast, M2 macrophages express a wide array of anti-inflammatory molecules, such as IL-10, TGF-β, and arginase1. In most tumors, the infiltrated macrophages are considered to be of the M2 phenotype, which provides an immunosuppressive microenvironment for tumor growth. Furthermore, tumor-associated macrophages secrete many cytokines, chemokines, and proteases, which promote tumor angiogenesis, growth, metastasis, and immunosuppression. Recently, it was also found that tumor-associated macrophages interact with cancer stem cells. This interaction leads to tumorigenesis, metastasis, and drug resistance. So mediating macrophage to resist tumors is considered to be potential therapy.